2012
DOI: 10.15580/gjss.2012.5.101912120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of women’s enterprises on household livelihoods and survival: Evidence from the North West Region of Cameroon

Abstract: The microenterprise sector has emerged as a major strategy to address the issues of unemployment and poverty challenging most developing economies. With limited alternatives to generate income on offer, the sector has become an attractive strategy to enhance the livelihoods of the poor as it provides low-income people with the opportunity to undertake income generation. Inspired by recent debates on the role of women's micro enterprise activity, the paper examines women's contribution to household survival thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This study also finds that the entrepreneurial activities of these women contribute to the larger economy through the promotion of tourism, the generation of employment and through export trade. Similar results are found for business women in Cameroon where Abonge (2012) observes that these women are, in a number of cases, the principal earners and sometimes the sole providers of the household, for both female-headed households and couple-headed households. In the case of couple-headed households, the situation is attributed to lack of employment for their spouses.…”
Section: Prior Researchsupporting
confidence: 79%
See 1 more Smart Citation
“…This study also finds that the entrepreneurial activities of these women contribute to the larger economy through the promotion of tourism, the generation of employment and through export trade. Similar results are found for business women in Cameroon where Abonge (2012) observes that these women are, in a number of cases, the principal earners and sometimes the sole providers of the household, for both female-headed households and couple-headed households. In the case of couple-headed households, the situation is attributed to lack of employment for their spouses.…”
Section: Prior Researchsupporting
confidence: 79%
“…Literature on the effect of women's business ownership on the welfare of the household is nevertheless limited. Some earlier research into welfare impact of women-owned businesses examined subjective well-being measures (Abonge, 2012;Misango and Ongiti, 2013;Ojo and Wurani, 2013). These studies are largely qualitative.…”
Section: Prior Researchmentioning
confidence: 99%
“…In a study carried out in the North West Region of Cameroon, Abonge (2012) found that micro and small-scale businesses have grown to be the mainstay of disadvantaged women entrepreneurs forced to run these businesses for home provisioning and as a method of obtaining employment for themselves. The ability of women to manage a business is generally seen as having the most significant positive impact on their ability to provide for basic household necessities.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Farming experience in Irish potato, the result in Table 1 indicated that, (67%) and (54%) of both the participating farmers and non-participating farmers had Irish potato farming experience between 1-10 years and 11-20 years, respectively. Abonge (2012) opined that farming experience is an important factor in determining both the productivity and the production level in farming. The result in Table 1 reveals that (55%) and (47%) of the participating farmers and non-participating farmers had secondary school education, which constituted the largest number of educational qualifications attained in the study area.…”
Section: Socio-economic Characteristics Of Participating and Non-part...mentioning
confidence: 99%